Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1139/cjb-2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

Grazing exclosures reveal divergent patterns of change in bunchgrass grasslands of Western Canada

Abstract: Thirty-six long-term (14–83 years) cattle grazing exclosures and adjacent grazed pastures spanning a climatic gradient from cooler–wetter to warmer–drier growing seasons in south-central British Columbia were compared for temporal vegetation change. Trajectories of temporal vegetation change from non-metric multidimensional scaling were mostly scattered for the grazed areas, but more directed toward the dominant grasses, primarily rough fescue (Festuca campestris) or Kentucky bluegrass (Poa pratensis), for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 96 publications
(157 reference statements)
0
4
0
Order By: Relevance
“…To maintain grassland resilience, light grazing combined with periodic low‐severity prescribed burning may be the optimal management practices for maintaining native bunchgrass cover while preventing encroachment of conifers and reducing excessive fuel accumulation. Light grazing regimes that leave adequate living plant material and litter cover are important for growth and recovery of native bunchgrasses in the grasslands of Interior BC (Bradfield et al, 2021; Cumming et al, 2016; McLean & Wikeem, 1985). In this study, we found that restoration activities including low‐severity prescribed fire disturbances and mechanical removal of dense stands of trees on historical grasslands are important practices for maintaining grassland resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain grassland resilience, light grazing combined with periodic low‐severity prescribed burning may be the optimal management practices for maintaining native bunchgrass cover while preventing encroachment of conifers and reducing excessive fuel accumulation. Light grazing regimes that leave adequate living plant material and litter cover are important for growth and recovery of native bunchgrasses in the grasslands of Interior BC (Bradfield et al, 2021; Cumming et al, 2016; McLean & Wikeem, 1985). In this study, we found that restoration activities including low‐severity prescribed fire disturbances and mechanical removal of dense stands of trees on historical grasslands are important practices for maintaining grassland resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Although the state and transition model may be appropriate to understand the phenomenon of coexisting grassland and forest states, we do not preclude the use of other theoretical frameworks to understand co‐occurring stable states in the forest–grassland mosaic. For example, community successional processes for the grassland state and the forest state are comprehensively documented (Bradfield et al, 2021; Hamilton et al, 2022; McLean & Tisdale, 1972; Simard, 2009; Twieg et al, 2007). Further, a change in state from grasslands to young forests reveals that new combinations of plant species can emerge, implicating individual‐based theories of ecology such as priority effects and historical contingencies (Drake, 1991; Fukami, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Spreading by rhizomes, Kentucky bluegrass will also form a continuous mulch on the surface which has been shown to regulate soil water and temperature dynamics (Avery et al, 2019), reduce plant diversity and germination (Halvorson et al, 2022), and lead to increased soil C and N (Sanderson et al, 2017;Hendrickson et al, 2021). Despite the documented decrease in Kentucky bluegrass from the Upper Grassland and Black Chernozem zone, this species has been increasing on mesic grasslands with and without grazing in both Alberta (Zapisocki et al, 2022) and BC (Bradfield et al, 2021;Hamilton et al, 2022), and throughout the Northern Great Plains (Toledo et al, 2014). Where present, the influence of Kentucky bluegrass needs to be taken into consideration in future studies on grassland SOC change and storage.…”
Section: Stock Comparison With Data Reported By Van Ryswyk Et Al (1966)mentioning
confidence: 99%
“…Like most grasslands in BC, the Lac du Bois Grassland has been severely degraded by heavy grazing during late 19 th to mid 20 th centuries. With the introduction of improved grazing strategies throughout south-central BC since the mid-1970s, that either reduce the grazing duration or alternate the season of grazing, there has been an increase in perennial bunchgrass cover and minimal differences in species richness and diversity between grazed and ungrazed sites (Bradfield et al, 2021). Specifically at Lac du Bois, livestock grazing is managed using a seasonal deferred grazing regime (Briske et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of community ecology are best studied through direct observational fieldwork or manipulation in the field or laboratory. For example, the effect of herbivores on woodland regeneration can be studied using exclosures (Dauwalter et al 2018;Bradfield et al 2021), while lab-based microcosm experiments can be useful for examining species' coexistence (e.g. Luckinbill 1973), competition (e.g.…”
Section: Community Ecologymentioning
confidence: 99%